Human adenovirus detection among immunocompetent and immunocompromised patients presenting acute respiratory infection - Watanabe,Aripuana (2013)
INTRODUCTION: Human adenoviruses (HAdV) play an important role in the etiology of severe acute lower respiratory infection, especially in immunocompromised individuals. The aim of the present study was detect the HAdV through different methods: direct fluorescence assay (DFA) and nested-polymerase chain reaction (PCR-nested) from patients with acute respiratory infection (ARI) up to 7 days of symptoms onset.METHODS:Samples (n=643) were collected from different risk groups during from 2001 to 2010: 139 adults attended in an Emergency Room Patients (ERP); 205 health care workers (HCW); 69 from Renal Transplant Outpatients (RTO); 230 patients in hematopoietic stem cell transplantation (HSCT) program.RESULTS:Among all patients (n=643) adenovirus was detected on 13.2% by DFA and/or PCR: 6/139 (4.3%) adults from ERP, 7/205 (3.4%) from HCW samples, 4/69 (5.8%) from RTO and 68/230 (29.5%) from HSCT patients. Nested PCR showed higher detection (10%) compared to DFA test (3.8%) (p < 0.001). HSCT patients presented significantly higher prevalence of HAdV infection.CONCLUSIONS:Adenovirus detection through nested-PCR assay was higher. However the inclusion of molecular method in laboratorial routine diagnostic should be evaluated considering the reality of each specific health service.